Short enantioselective total synthesis of (R)- and (S)-pipecolic acid - Chavan, Subhash P.; Khairnar, Lalit B.; Chavan, Prakash N.; Kalbhor, Dinesh B. (Tetrahedron-Asymmetry, 2014)
A convenient and practical total synthesis of (R)- and (S)-pipecolic acid has been achieved by utilizing chiral cis-aziridine-2-carboxylate as the common synthetic precursor. The synthesis involves regioselective reductive cleavage of the aziridine ring and Wittig olefination as key reactions. (C) 2014 Elsevier Ltd. All rights reserved.

Stereospecific synthetic approach towards tamiflu using the ramberg-backlund reaction from cysteine hydrochloride - Chavan, Subhash P.; Chavan, Prakash N.; Gonnade, Rajesh G. (RSC Advances, 2014)
The stereospecific formal synthesis of Tamiflu from L-cysteine hydrochloride as the chiral source is described. The notable feature of the present strategy is the Ramberg-Backlund reaction and Sharpless-Reich protocol as the key chemical transformations to access the cyclohexene skeleton of Tamiflu.